Effect of CuI concentration on structural and optical properties of PVA: CuI nanocomposites - Suhail, Mahdi Hasan (Iraqi Journal of Physics, 2019)
The nanocomposite on the base of synthesis Copper iodide nanoparticles and polyvinyl alcohol (PVA/CuI) with different concentration of CuI were obtained using casting technique. PVA/CuI polymer composite samples have been prepared and subjected to characterizations using FTIR spectroscopy, The FTIR spectral analysis shows remarkable variation of the absorption peak positions with increasing CuI concentration. The obtained results by X-ray diffraction indicated the formation of cubic CuI particles. The effects of CuI concentrations on the optical properties of the PVA films were studied in the region of wavelength, (190-1100) nm. From the derivation of Tauc’s relation it was found that the direct allowed transitions was more probable in PVA/ CuI nanocomposite. The results indicate that the obtained values of optical absorption edge, and energies band gap decreases from 4.05 to3.89 eV for direct transitions with the increasing salt contents.